ANALISIS DEFORMASI GUNUNGAPI MERAPI DENGAN METODE GEODETIK-GPS - MA'RUF, BILAL
Understanding of magmatic phenomena and monitoring of Merapi Volcano will require a deformation study. Deformation study is a multidiscipline study. Geodesy is one of a discipline that deals with deformation from geometric point of view, in terms of determining the magnitude, pattern, and parameters of the deformation. The well known geodetic method which is used in monitoring the deformation of Merapi Volcano is Global Positioning System (GPS). This research emphasizes on the analysis of deformation of Merapi Volcano with the geodetic method using GPS surveys. GPS monitoring network is established covering the body of Merapi Volcano and its surrounding. The coordinates of the points of the monitoring network obtained from GPS surveys, are used to determine the magnitude and direction of the vector displacements of the points. These vector displacements are useful information for developing the model of deformation analysis which then is used to determine deformation parameters of Merapi Volcano. This research concludes that, 1) the single frequency GPS receiver can be used to monitor the deformation of Merapi Volcano, 2) during the period of November 1996-March 1998, Merapi Volcano had exploded twice and deformed. This can be proved from geodetic and physics points of view. From the geometric point of view the magnitude of vector displacement, deformation parameters, as well as the principal strain show significance values; while from physics point of view Merapi shows the growing dome and it has exploded twice in January 17, 1997 and July, 1998, 3) the characteristics of deformation can be geometrically useful to predict the physical activities of Merapi Volcano, 4) the study of deformation model of Merapi Volcano can be approached by two models. The first is a model that includes translation, strain and rotation, while the second one is a model that includes just strain and rotation (no translation). Based on geological and geophysical information, the second model seems to be more realistic for describing the deformation of Merapi Volcano.